Role of Internet Accessibility in Reducing the Poverty rates in Java; a Spatial Approach - Hidayat, Andhy; Prasetya, Ferry; Pangestuty, Farah Wulandari (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2021)
The poverty reduction rate in Java was considered very low, thus requiring new strategies and policies, such as the improvement of internet accessibility. This study, using the 2018 National Socio-Economic Survey (SUSENAS) data, aimed to examine the role of internet accessibility to reduce poverty rates in Java through a spatial approach. The results showed that internet accessibility had a significant effect on the reduction of poverty rates in Java. It also found that the poverty rates in an area in Java were influenced by the types of works of household heads in the same location and the poverty rates in neighboring areas (spatial spillover effects). This study recommended that the Government, in reducing poverty rates, focuses on providing internet infrastructure and, more, on spatial aspects